Selection of Primary Land Transportation Fleet Using Vehicle Operational Cost (VOC) Method in Logistics Companies - Ardiansyah, Dicky Candra; Jasmine, Tamara Latifah; Sekarningtyas , Hikmah (Faculty of Engineering, Andi Djemma University, 2025)
The selection of transportation fleets plays a crucial role in determining the cost efficiency of logistics operations. This study aims to evaluate the feasibility of investing in company-owned vehicles compared to using third-party rental services on the Bandung–KTSH route operated by the Bandung Branch Office of PT Pos Logistik Indonesia. Using a quantitative approach with a causal associative design, this research applies the Vehicle Operating Cost (VOC) method supported by investment feasibility analysis tools including Cash Flow, Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP). The analysis shows that the average daily operational cost of company-owned vehicles reaches IDR 1.904.479, which is higher than the rental cost of IDR 1.865.385 per day. Additionally, the results show a negative NPV (–IDR 150,550,343), negative IRR (–35.1%), and an unattainable payback period within the 5-year investment horizon. Therefore, it is concluded that using leased vehicles is more cost-efficient than investing in company-owned trucks for this specific route.